Acute axillohumeral thrombosis in a wearer with crutches - Méndez, Hugo; Porras, Yamandú (Cirugía del Uruguay, 2020)
40-year-old patient (IRV) who, due to a polio sequela, has supported a crutch in his left armpit since childhood (4 years), which never caused him disorders until a few days ago, when he began to feel paresthesia in his fingers hand (tingling, coldness) which he relieves by lying down and putting his hand on the decline ...